2000
DOI: 10.1067/mpr.2000.107192
|View full text |Cite
|
Sign up to set email alerts
|

In vitro comparison of fluoride release of six direct core materials

Abstract: Fuji II LC released the most fluoride and was significantly different from the other materials tested. The maximum amount of fluoride was released by 5 of the 6 materials during the first 24 hours and gradually tapered over the 89-day testing period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Galvan et al [54] observed that releasing fluoride ions dental materials showed the highest activity on the first day after polymerization, followed by dropping for the next 90 days of the experiment remaining minimum level of F − ion release. It is expected that such materials would serve as fluoride reservoirs and will remain cariostatic.…”
Section: Discussionmentioning
confidence: 99%
“…Galvan et al [54] observed that releasing fluoride ions dental materials showed the highest activity on the first day after polymerization, followed by dropping for the next 90 days of the experiment remaining minimum level of F − ion release. It is expected that such materials would serve as fluoride reservoirs and will remain cariostatic.…”
Section: Discussionmentioning
confidence: 99%